INTERPRETATION OF VIOLENCE IN HUSBAND-WIFE RELATIONS: A COMPARATIVE ANALYSIS OF AT-THOBARI AND SAYYID QUTHB'S INTERPRETATION OF QS. AL-NISĀ' [4]: 19 & 24 - Hambali Hambali; Ahmad Syukri Saleh; Firhat Abbas (Program Pascasarjana UIN Sumatera Utara, 2025)
This study examines the interpretation of the Qur'an on domestic violence by husbands through a comparative study of the views of al-Ṭabari and Sayyid Quṭb on QS. al-Nisa' [4]:19 and [4]:34. The background of this study is based on the rise of domestic violence (KDRT) which is often rooted in textual understanding and patriarchal bias towards the verses of the Qur'an, especially regarding the concepts of qawwamūn and daraba. In this context, the Qur'an actually emphasizes the values of sakinah, mawaddah, and rahmah as the foundation of an ideal family that is just, equal, and free from violence. This study aims to clarify the relationship between sacred texts, interpretations, and social practices in efforts to prevent domestic violence by exploring how the two commentators interpret the key concepts of qawwamūn, nushūz, and daraba along with their ethical and normative implications for family life. The research method uses a qualitative approach based on library research with a comparative-thematic analysis model (mawḍū‘i). The results show that both commentators reject domestic violence and emphasize the family as a spiritual and moral institution based on justice and compassion. Al-Ṭabari presents a legal-normative framework by interpreting qiwamah as a mandate of responsibility limited by ma‘rūf and emphasizing the discipline of worship and justice in household relations. Meanwhile, Sayyid Quṭb emphasizes the ethical-spiritual horizon, interpreting qiwamah as a mandate of service and mu‘asyarah bil-ma‘rūf as an anti-violence principle that fosters mercy. Both are combined in the Qur'anic vision that makes the family the center of civilization and a space for the actualization of divine values in human relations. The novelty of this research lies in the effort to integrate classical and modern interpretations into the maqasidi interpretation paradigm which emphasizes the values of mercy, justice, and humanity as the foundation for forming a harmonious family free from violence.